Pengaturan Aliran Daya Reaktif Dengan Transformator Regulasi Jenis Pengatur Tegangan Pada Jaringan Sistem Tenaga Listrik - Despa, Dikpride (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2009)
Reactive power flow regulation is power system is required to improve voltage profile and reduce system losses. Reactive power flow regulation is done using correct tap setting on the regulating transformer. The study is conducted through literature survey and simulation using ETAP. The result shows that correct tap setting on the regulated bus, voltage increases up to theallowable limits 10 percents over nominal voltage and at the same time reduce system losses. Finally, tehe result also shows that about 77,07percents of total reactive power required by load can be met by the transformer.